Phylogeography and genetic structure of the threatened Canarian Juniperus cedrus (Cupressaceae). (17th June 2014) - Rumeu, Beatriz; Vargas, Pablo; Jaén‐Molina, Ruth; Nogales, Manuel; Caujapé‐Castells, Juli
<x xml:space="preserve">Abstract</x> We used plastid sequences (trnL, trnL‐trnF, petN‐psbM and trnT‐trnL) to infer the phylogenetic relationships and inter‐island connections of the Canarian Juniperus cedrus, and AFLP fingerprints to assess its genetic diversity patterns. Maximum Likelihood, Maximum Parsimony and Bayesian methods suggest independent colonization events for the three Macaronesian junipers and support the monophyly of J. cedrus. Plastid sequences reveal a low genetic diversity (three haplotypes) and do not provide sufficient information to resolve its temporal and geographical origin. AFLPs indicate a greater isolation in J. cedrus than in other Macaronesian trees with similar distributions and dispersal syndromes. Gran Canaria harbours the least genetically diverse population, which justifies immediate conservation actions. This island and Tenerife also show independent genetic structure, meaning that genetic exchange from other islands should be avoided in eventual reinforcements. Populations from La Palma and La Gomera show the highest genetic diversity levels and number of polymorphic AFLPs, probably because a lower incidence of felling has allowed a less dramatic influence of genetic bottlenecks. We suggest that management efforts should prioritize populations from these islands to preserve the evolutionary potential of the species, but we also stress the importance of knowledge of the evolutionary history, genetic structure and ecological interactions in conservation strategies. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 175, 376–394.